Looking at underrepresentation of women in high-profile jobs in Iceland from a social identity theory perspective : is gender a liability? - Anna H. Johannessen 1990- (2019)
The objective of this research was to explore the various factors that contribute to the underrepresentation of women in leadership positions in Iceland where social identity theory was used as a leading theory in the research. Two research questions were put forward in the introduction chapter: RQ1: From a social identity theory perspective, do employers view women as members of an in-group or out-group regarding leadership positions in Iceland? RQ2: What corporate environmental factors lead to women falling behind in attaining high- profile jobs in Iceland? The theoretical review focuses on relevant theories, researches and numerous barriers that women have to overcome. A multiple case study was conducted where ten human resource personnel were participants in various organizations in Iceland. The results to research question one revealed that according to the social identity theory, women are perceived as out-group members when it comes to attaining leadership positions. The results for research question two are similar to existing literature where women in Iceland face comparable barriers as women in other countries. An addition to the literature was developed by the researcher, where developmental opportunities are needed from the bottom up inside organizations to increase the proportion of women in leadership positions. Having more women would work against barriers such as stereotypes and prejudice. Propositions for organizations was mentioned to implement gender equality in leadership positions, limitations to the research was stated with ideas for future research. Keywords: Social identity theory, in-group/out-group, underrepresentation of women, leadership, developmental opportunities for women.